Structural Shift in Demand for Food: Projections for 2020 - Surabhi Mittal (Indian Council for Research on International Economic Relations (ICRIER), 2006)
Knowledge of demand structure and consumer behaviour is essential for a wide range of development policy questions like improvement in nutritional status, food subsidy, sectoral and macroeconomic policy analysis, etc. An analysis of food consumption patterns and how they are likely to shift with changes in income and relative price is required to assess the food security-related policy issues in the agricultural sector. With high growth rates in the agricultural sector, the average per capita income in the country shows an increase, accompanied by a fall in the per capita consumption of staple food. In this background the present study diagnoses the food basket of households in rural and urban areas under different expenditure groups in the last two decades and tries to investigate the driving force for these changes by computing the demand elasticities that explain the level of demand for the commodities by an individual consumer given the structure of relative prices faced, real income and a set of individual characteristics such as age, type of household [expenditure groups] and geographical environment [rural or urban]. The study projects the prospects of the food demand scenario in the country in 2020. And, finally, aims at finding answers to some of the most debatable issues relating to the country's food security, decline in cereal consumption and implications on poverty. The study uses data from the consumer expenditure survey of the National Sample Survey [NSS] rounds number 38, 43, 50 and 55
Keywords: Q11; Q18; 330; Household Food Consumption; Demand Elasticity; Decomposition; Demand Projections; Quadratic AIDS Model